Electrochemistry of Zinc Electrodes in Acetone‐Zinc Halide Electrolytes. Issue 45 (1st December 2021) - Sun, Yu; Xie, Minghao; Kong, Shuting; Wang, Jie; Dong, Dongqi; Xuan, Cuijuan; Gong, Liangyu; Ma, Chuanli; Su, Linghao
Abstract: The effects on the electrochemistry of zinc electrode in acetone‐zinc halide electrolyte are discussed. Cyclic voltammetry and galvanostatic tests show that the reversibility of zinc deposition and dissolution in ZnCl2 is superior to ZnBr2 electrolyte. In ZnCl2 acetone electrolyte, 1 M is the optimal concentration in which Zn−Zn symmetric battery reveals reversible charge/discharge cycles for 960 hours. Powder XRD detects a by‐product Zn5 (OH)8 Cl2 ⋅H2 O created on zinc surface during long‐term charge/discharge process, indicating a certain degree of interaction between zinc electrode and acetone solvent. Abstract : The usage of cheap acetone as electrolyte solvent for zinc‐ion battery and the effects on the electrochemical performances of Zn electrode in acetone‐zinc halide electrolyte are investigated. Both type and concentration of zinc salts have influences on the plating/stripping of zinc. Acetone‐ZnCl2 electrolyte displays a stable electrochemical window of 2.03 V. In acetone‐zinc halide electrolytes, ZnCl2 is superior to ZnBr2 and 1 M ZnCl2 is optimal.